L-arginine improves endothelium-dependent vasodilation in hypercholesterolemic humans. - Creager, M A (1992)
Endothelium-dependent vasodilation is impaired in hypercholesterolemia, even before the development of atherosclerosis. The purpose of this study was to determine whether infusion of L-arginine, the precursor of the endothelium-derived relaxing factor, nitric oxide, improves endothelium-dependent vasodilation in hypercholesterolemic humans. Vascular reactivity was measured in the forearm resistance vessels of 11 normal subjects (serum LDL cholesterol = 2.76 +/- 0.10 mmol/liter) and 14 age-matched patients with hypercholesterolemia (serum LDL cholesterol = 4.65 +/- 0.36 mmol/liter, P < 0.05). The vasodilative response to the endothelium-dependent vasodilator, methacholine chloride, was depressed in the hypercholesterolemic group, whereas endothelium-independent vasodilation, induced by nitroprusside, was similar in each group. Intravenous administration of L-arginine augmented the forearm blood flow response to methacholine in the hypercholesterolemic individuals, but not in the normal subjects. L-arginine did not alter the effect of nitroprusside in either group. D-arginine had no effect on forearm vascular reactivity in either group. It is concluded that endothelium-dependent vasodilation is impaired in hypercholesterolemic humans. This abnormality can be improved acutely by administration of L-arginine, possibly by increasing the synthesis of endothelium-derived relaxing factor.